Na tropach antropologicznego aspektu rewitalizacji = Tracing the anthropological aspect of revitalisation - Pokrzyńska, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article discusses the temporal aspect of culture. The author presents culture in the context of tradition shaping, reinterpretation processes and returns to the abandoned heritage. She emphasizes one of the meanings of the term revitalization (hardly present in today?s public discourse), i.e., restoring the topicality of the elements of old culture. Revitalization is interpreted as bringing well-known culture (ideas, values, patterns of thinking or acting, social norms, artefacts of material culture, etc.) back to life. The author invokes the definition of revitalization known in anthropology and points to the importance of social movement in revitalization processes. She gives examples of contemporary revitalization activities in various dimensions of life (e.g., agriculture, lifestyle, aesthetics, architecture, landscaping).
Keywords: dziedzictwo kulturowe; tradycja; ruch społeczny; rewitalizacja; cultural heritage; tradition; social movements; revitalisation